Depth psychology, cult survivors, and the role of the daimon : oppression, agency, and authenticity - Quennec, Linda, 1969- (New York, NY : Routledge, 2024)
"This book explores the possibilities that exist for navigating out of and away from multiple levels of oppression through memoir-based research. It considers how those raised in oppressive, high-demand communities, colloquially referred to as "cults" can emancipate themselves from controls and expectations inculcated from early childhood, and examines processes surrounding the psychological reclamation of self. Exploring and metaphorically tending to an orienting psychological dynamic that the ancient Greeks related to as "the daimon" and using the perspectives of Jungian and post-Jungian depth psychology, the author investigates how subjects can reclaim agency and avoid excessive control over their thoughts, attention, and life's intentions. They suggest that depth psychologically-oriented modes can be used to this attunement, and explore this notion through a study of memoirs of individuals who were raised in "cults". Suggesting a more aligned approach to working with varying levels of psychological constraint, and utilising a phenomenological hermeneutic study, it will appeal to scholars and professionals in depth psychology and other psychological orientations, as well as individuals who are interested in more deeply understanding the psychological mechanisms involved in leaving a high-demand group or other oppressive situations"--
Keywords: Jungian psychology; Oppression (Psychology); Cults -- Psychology; RELIGION / Cults